Inovasi Metode Blended Learning di Sekolah Tinggi Teologi IKSM Santosa Asih - Muanley, Yonas (Voice of HAMI: Jurnal Teologi dan Pendidikan Agama Kristen, 2020)
Internet technology has influenced various fields of human life, especially in the world of education, including in IKSM Santosa Asih Theological Seminary. The development of internet technology has changed learning methods, such as conventional methods to future learning or blended learning. Blended Learning method is influenced by the development of the internet. These developments are used innovatively in learning methods that are relevant to the context of today's development that is more utilizing digital technology. Every Theological College has a website but it is not used as a means of online learning with a blended learning method, lecturers rarely use blogs with the blogspot and wordpress platforms for online learning, learning is done conventionally (face to face in the lecture hall), utilizing mobile phones in learning or mobile learning is rarely done in Theological Seminary. While in the world of general education, blended learning methods, including mobile learning have long been carried out. Theology students and lecturers, no one do not use a cellphone, but not many use cellphones for online learning. Abstrak Teknologi internet telah mempengaruhi berbagai bidang kehidupan manusia, khususnya di dunia pendidikan, termasuk Sekolah Tinggi Teologi IKSM Santosa Asih. Perkembangan teknologi internet telah mengubah metode pembelajaran, seperti metode konfensional ke pembelajaran masa depan atau blended learning. Metode Blended Learning dipengaruhi oleh perkembangan internet. Perkembangan tersebut dimanfaatkan secara inovatif dalam metode pembelajaran yang relevan dengan konteks perkembangan zaman kini yang lebih memanfaatkan teknologi digital. Setiap Sekolah Tinggi Teologi memiliki website namun tidak dipakai sebagai sarana pembelajaran online dengan metode blended learning, para dosenpun jarang memanfaatkan blog dengan platform blogspot dan wordpress untuk pembelajaran online, pembelajaran dilakukan secara konfensional (tatap muka di ruang kuliah), pemanfaatkan handphone dalam pembelajaran atau mobile learningpun jarang dilakukan di STT. Sementara di dunia pendidikan umum, metode blended learning, termasuk mobile learning telah lama dilakukan. Para mahasiswa dan dosen Teologi, tidak ada yang tidak menggunakan handphone, namun belum banyak yang memnafaatkan handphone untuk pembelajaran online.